Different Strategies for Molecular Differentiation of Mycobacterium bovis Strains Isolated in Sardinia, Italy - Sechi, Leonardo A. (American Society for Microbiology, 1999)
Different genetic markers were used to analyze 22 Mycobacterium bovis strains isolated from cattle in Sardinia and one human isolate. IS6110 DNA fingerprinting differentiated the strains into six patterns, whereas with enterobacterial repetitive consensus sequence primers produced seven clusters. PCR ribotyping followed by digestion with HaeIII and PvuII produced five and seven patterns, respectively. PCR with the (GTG)(5) oligonucleotide primer showed the best discriminatory power, generating eight clusters among the strains analyzed.